Theatre and curriculum: the case of basic education in Mexico - Retes Campesino, Juan Claudio (Historia y Memoria de la Educación, 2016)
This paper comprehends an historical overview of the role that theatre has played in the Mexican elementary school curriculum. Such a history is recent, given that artistic education —and theatre within it— were only incorporated into official programs well into the 20th century